1993
DOI: 10.1042/bj2960309
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin inhibits voltage-activated calcium channels in adrenal glomerulosa cells

Abstract: Thapsigargin, an inhibitor of the microsomal Ca2+ pumps, has been extensively used to study the intracellular Ca2+ pool participating in the generation of the agonist-induced Ca2+ signal in various cell types. A dual effect of this agent was observed in bovine adrenal zona glomerulosa cells. At nanomolar concentrations, thapsigargin stimulated a sustained Ca2+ influx, probably resulting from Ca(2+)-store depletion. In contrast, when added at micromolar concentrations, thapsigargin prevented the rise in cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 26 publications
(30 reference statements)
3
26
1
Order By: Relevance
“…Together these data indicate that Ang II-stimulated StAR promoter activity is not dependent upon reaching a threshold level of [Ca 2ϩ ] i . Previous studies reported Tg increased aldosterone production in both primary cultures of bovine and rat adrenal glomerulosa cells (5,39,40). However, a significant Tg response in bovine adrenal cells required 8 mM K ϩ in the medium, and our culture conditions had 4 mM K ϩ , which may account for the difference.…”
Section: Discussioncontrasting
confidence: 46%
“…Together these data indicate that Ang II-stimulated StAR promoter activity is not dependent upon reaching a threshold level of [Ca 2ϩ ] i . Previous studies reported Tg increased aldosterone production in both primary cultures of bovine and rat adrenal glomerulosa cells (5,39,40). However, a significant Tg response in bovine adrenal cells required 8 mM K ϩ in the medium, and our culture conditions had 4 mM K ϩ , which may account for the difference.…”
Section: Discussioncontrasting
confidence: 46%
“…Dose dependency of the effects of thapsigargin on cytosolic free Ca 2ϩ concentrations has been observed in mammalian cells. At nanomolar concentrations, thapsigargin induced sustained Ca 2ϩ release, whereas at micromolar concentrations it decreased intracellular Ca 2ϩ concentrations by blocking voltage-activated channels (Rossier et al, 1993). Although thapsigargin treatments cannot differentiate between intra-and extracellular Ca 2ϩ sources, these results indicate that changes in intracellular Ca 2ϩ are likely to contribute to Ppc1 induction.…”
Section: Resultsmentioning
confidence: 65%
“…Thapsigargin has been reported to inhibit voltage-gated Ca¥ channel (VGCC) activity (Rossier et al 1993); however, such an action remains to be demonstrated in central neurones (Simpson et al 1995). In the present investigation thapsigargin had no obvious inhibitory action on VGCC-mediated Ca¥ elevations at the doses used: exposure of cells to thapsigargin (2-10 ìÒ) in the presence of 25 mÒ K¤ often increased intracellular Ca¥ levels but never decreased them ( Fig.…”
Section: Effects Of Thapsigarginmentioning
confidence: 56%